Examining the Causes and Economic Impact of Rural-Urban Migration - Mr. Simon Wangombe Ngari; Prof. L. P Mureithi; Dr. S. M Nyandemo (Examining the Causes and Economic Impact of Rural-Urban Migration, Edition 1, 2025)
This research paper aims to study migration from rural to urban areas with the main concern that by the year 2050, it’s expected that 60% of the total world population will reside in urban areas. This is by all means a major transition from the 1950s when only 30% of the population resided in urban areas. The major concern here is whether developing economies will be prepared enough to cope with the socio-economic and political implications of this transition. This study aims at adding value to already existing literature on migration patterns by looking at other possible factors that may cause rural-urban migration like social ties and relationships among other traditional factors like age, sex, marital status, income expectations and family size. This research critically examines the effects of education on migration decisions by analyzing data on the level of education attained by the time a migrant makes a decision to migrate. The study found that most of the migrants to the urban areas have attained little or no education at all and the majority only have a primary level of education. The study also examines the socio-economic and environmental concepts associated with rural-urban migration such as the mushrooming of slum dwellings, urban unemployment, crime, environmental degradation and other social vices like drug peddling hawking and prostitution. This study aims at suggesting policy recommendations based on the findings which can be of use to policymakers and the Government as they try to tackle this problem. Of great importance as found out in the study is the need to develop infrastructure in the rural areas, and create income-generating activities and employment opportunities in these areas in order to minimize urban migration. This should be followed by a Government-regulated and planned expansion of the urban informal sector to control the emergence of slum dwellings and unplanned economic activities. Finally, this study proposes areas that require further research such as the effect of technology, digitization of the economy effects of internet connectivity and mobile banking in influencing future migration patterns from rural to urban areas.